The Optics of Leadership: Visual Representation in the 2024 Indonesian Presidential Campaign - Abdullah, Irwan; Afriadi, Dedy; Yusuf, Mirna; Susanto, Mikke; Fawaid, Achmad (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This research explores the significant role played by visual representation in Indonesian presidential election campaigns. By addressing a gap in existing literature that has largely overlooked the importance of visual representation in shaping voter preferences, this study contributes to a deeper comprehension of the underlying dynamics. Through the analysis of visual data, it becomes apparent that effective visual representation has the potential to enhance a candidate’s image, sway voter emotions, and ultimately impact electability. Key findings highlight variations in communication strategies employed by presidential candidates, emphasizing the crucial role of visual representation in political campaigns and the complex array of factors influencing public decision-making. The dominance of visual communication emerges as a critical factor in shaping public opinion and determining voter preferences. This study provides scholarly insights into the mechanisms involved in visual communication within political processes, particularly within the context of leadership campaigns.